L-plastin phosphorylation: a novel target for the immunosuppressive drug dexamethasone in primary human T cells - Wabnitz, Guido H.; Michalke, Felix; Stober, Christoph; Kirchgessner, Henning; Jahraus, Beate; van den Boomen, Dick J. H.; Samstag, Yvonne (European journal of immunology, 2011)
Activation of naïve T cells requires costimulation via TCR/CD3 plus accessory receptors, which enables the dynamic rearrangement of the actin cytoskeleton and immune synapse maturation. Signaling events induced following costimulation may thus be valuable targets for therapeutic immunosuppression. Phosphorylation of the actin-bundling protein L-plastin represents such a costimulatory signal in primary human T cells. Phosphorylated L-plastin has a higher affinity toward F-actin. However, the importance of the L-plastin phosphorylation for actin cytoskeleton regulation upon antigen recognition remained unclear. Here, we demonstrate that phosphorylation of L-plastin is important for immune synapse maturation. Thus, expression of nonphosphorylatable L-plastin in untransformed human peripheral blood T cells leads to reduced accumulation of LFA-1 in the immune synapse and to a diminished F-actin increase upon T-cell activation. Interestingly, L-plastin phosphorylation is inhibited by the glucocorticoid dexamethasone. In line with this finding, dexamethasone treatment leads to a reduced F-actin content in stimulated T cells and prevents maturation of the immune synapse. This inhibitory effect of dexamethasone could be reverted by expression of a phospho-mimicking L-plastin mutant. In conclusion, our data introduce costimulation-induced L-plastin phosphorylation as an important event for immune synapse formation and its inhibition by dexamethasone as a novel mode of function of this immunosuppressive glucocorticoid.
Gesehen am 04.11.2022